THE EFFECTIVENESS OF MUROTTAL AL-QUR’AN THERAPY ON INCREASING STUDENTS LEARNING CONCENTRATION - Binti Nurhalimah; Dira Utami; Rensi Tiara Amelia; Yayu Indriani (CV. Doki Course and Training, 2023)
Success in learning can be achieved if you have followed the stages in the learning process, one of which is learning concentration. The purpose of this study was to determine the effectiveness of the effect of murottal al-qur'an therapy in increasing the concentration of learning in students. The number of subjects in this study amounted to 30 students of the Faculty of Psychology, Raden Fatah State Islamic University, Palembang. The experimental research design used was a one group pretest-posttest design. The murottal Al-Qur'an that is played is Surah Al-Waqiah which has a duration of 15 minutes 52 seconds using audio speaker media for 5 days. Data were analyzed using the Wilcoxon test with the help of SPSS version 22.0. The results of data analysis in this study obtained ρ value = 0.000 or ρ < 0.05 so it can be concluded that murottal al-qur'an therapy is effective in increasing student learning concentration.